Characteristics Of Exhibiting The Physical Capabilities Of Miners Of Different Professions In Adverse Environmental Conditions - O.S. Jumanov (Academia One Publishing, 2023)
Coordination abilities of miners, compensatory capabilities of miners, functional capabilities of miners depending on the length of service, some physiological changes in miners depending on the length of service and professional orientation, functional indicators of miners engaged in various cleaning operations, blood pressure of miners at a high rate of work.
Keywords: cleaning; length; capabilities